Pengaruh Kompetensi terhadap Kepuasan Kerja dan Work Engagement Karyawan UKM Kluster Hasil Pengolahan Perikanan di Bogor - Arvina Utami; Anggraini Sukmawati (IPB University, 2018)
The number of SMEs and amount of processed fish products in the city of Bogor is potential for the development of fish processing SMEs. SMEs need employees who are satisfied with their job and engaged with their work to maximize the development of their potential. The purpose of this study was to analyze the effects of competence and compensation on the job satisfaction and work engagement of employees of fish processing SMEs in Bogor. The sampling method used was a non-probability sampling technique, namely the census technique. The data processing and analysis methods were validity and reliability testing using SPSS, descriptive analysis, and Structural Equation Modeling (SEM) using SmartPLS. The descriptive analysis results showed the perceptions of employees towards competence, compensation, job satisfaction and work engagement.The SEM results show that job satisfaction was affected by competence and compensation. Work engagement was affected by competence and job satisfaction but it was not affected by compensation.